2006
DOI: 10.4319/lo.2006.51.6.2734
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrodynamics on the mass transfer of dissolved inorganic carbon to the freshwater macrophyte Vallisneria americana

Abstract: The combined effects of water velocity (U) and dissolved inorganic carbon (DIC) concentration on photosynthesis rates of Vallisneria americana were investigated. The net photosynthesis rate or O 2 flux (J obs ) from leaves increased with U from 0.20 6 0.01 (mean 6 standard error) mmol m 22 s 21 at U 5 0 m s 21 (i.e., in stagnant water) to 2.1 6 0. Sc 0.33 were higher than predicted for a laminar flat plate boundary layer, indicating that physicochemical activity, such as photosynthesis, influenced Sh x . The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(87 citation statements)
references
References 53 publications
5
81
1
Order By: Relevance
“…For example, in the red alga Laurencia brongniartii, the uptake kinetics were linear for nitrate and nonlinear for ammonium (Nishihara et al, 2005), whereas nonlinear kinetics were observed for both nutrients in the brown alga Scytothamnus australis (Phillips and Hurd, 2004). Indeed, physiology ultimately determines the rate of such processes; however, the transport of nutrients to the surface of aquatic macrophytes governs whether the process is kinetically or mass transfer limited (Sanford and Crawford, 2000;Nishihara and Ackerman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the red alga Laurencia brongniartii, the uptake kinetics were linear for nitrate and nonlinear for ammonium (Nishihara et al, 2005), whereas nonlinear kinetics were observed for both nutrients in the brown alga Scytothamnus australis (Phillips and Hurd, 2004). Indeed, physiology ultimately determines the rate of such processes; however, the transport of nutrients to the surface of aquatic macrophytes governs whether the process is kinetically or mass transfer limited (Sanford and Crawford, 2000;Nishihara and Ackerman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2). Our flow-mediated response was similar to the respiratory response of corals (Finelli et al, 2006;Patterson and Sebens, 1989;Patterson et al, 1991), nutrient uptake in seagrasses (Cornelisen and Thomas, 2004) and the photosynthetic response in aquatic plants (Nishihara and Ackerman, 2006;Stewart and Carpenter, 2003).…”
Section: −1mentioning
confidence: 57%
“…For instance, uptake of nutrients in freshwater plants has been shown to occur more slowly than does transport across their diffusional boundary layers (Nishihara and Ackerman, 2006). Reaction kinetics, in this case, may be more limiting than any rate of mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In general, water movement on a small scale has positive effects on nutrient uptake and metabolism due to the reduction of thickness of diffusion boundary layer around leaves (Madsen et al, 1993;Nishihara and Ackerman, 2006). However, water movement does not necessarily enhance nutrient uptake; it can inhibit plant physiological processes becoming a stress to the plants.…”
Section: Introductionmentioning
confidence: 99%